2021
DOI: 10.3390/ani11113158
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake and Deconjugation of Androstenone Sulfate in the Adipose Tissue of the Boar

Abstract: Boars express high testicular levels of sulfotransferase enzymes, and consequently, the boar taint causing compound androstenone predominantly circulates as a steroid sulfate. Androstenone sulfate is suspected to function as a steroid reservoir that can be deconjugated to provide a source of free androstenone for accumulation. Therefore, the purpose of this study was to characterize the uptake and deconjugation of androstenone sulfate in the adipose tissue of the boar. Real-time PCR was used to quantify the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…No significant differences in skatole levels or in the sensory perception of the panellists were detected between the individual muscles. According to more recent studies [ 9 , 32 ], the level of boar taint components in fat, lean tissue and plasma may be affected by the presence of other compounds related to boar taint. One of these compounds is androstenone sulphate, which contributes significantly to the free androstenone content in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences in skatole levels or in the sensory perception of the panellists were detected between the individual muscles. According to more recent studies [ 9 , 32 ], the level of boar taint components in fat, lean tissue and plasma may be affected by the presence of other compounds related to boar taint. One of these compounds is androstenone sulphate, which contributes significantly to the free androstenone content in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…leading to a poorer correlation). Such conjugates include androstenone sulfates such as androst-3-enol-3-sulfate and androstenone-4-sulfate (Bone & Squires, 2021;Squires et al, 2020). Secondly, correlation is lower at higher levels of androstenone than at lower ones.…”
Section: Analysis Of Skatole and Androstenone Emissionsmentioning
confidence: 99%
“…This suggests that the sulfoconjugation of androstenone and its metabolites during Phase II metabolism is essential for reducing the development of boar taint. However, we have recently shown that androstenone sulfate can be transported into the adipose tissue and deconjugated by the enzyme steroid sulfatase (STS) [61]. The deconjugation of androstenone sulfate was positively correlated with fat androstenone concentrations in early but not late-maturing boars, which suggests that the sulfoconjugation of the 16-androstene steroids may not reduce boar taint development in all animals.…”
Section: Nuclear Receptor-mediated Effects On Androstenone Metabolismmentioning
confidence: 99%